Bright and fast-response perovskite light-emitting diodes with an ICBA:modified-C60 nanocomposite electrical confinement layer. Issue 6 (5th February 2020) - Tsai, Chia-Lung; Lu, Yi-Chen; Chiang, Shou-En; Yu, Chih-Min; Cheng, Hsin-Ming; Hsu, Ching-Ling; Chiu, Kuo Yuan; Chang, Sheng Hsiung
Abstract : Bright and fast-response CH3 NH3 PbBr3 perovskite light-emitting diodes (PeLEDs) are realized by using ICBA:modified C60 (MC60 ) nanocomposites as the hole blocking layer (HBL) and electron transport layer (ETL). Abstract : Bright and fast-response CH3 NH3 PbBr3 perovskite light-emitting diodes (PeLEDs) are realized by using ICBA:modified C60 (MC60 ) nanocomposites as the hole blocking layer (HBL) and electron transport layer (ETL). The photoluminescence spectrum shows that the use of hydrophilic MC60 in the ETL helps the surface passivation of the perovskite layer. In addition, the photoelectron spectra and water-droplet contact angle images show that the use of the ICBA:MC60 nanocomposite ETL can simultaneously confine the electrons and holes in the perovskite layer, which boosts the injected electron–hole radiative recombination efficiency and thereby increases the electroluminescence from 1 cd m −2 to 2080 cd m −2 at 6 V when the ICBA:3, 5OEC60 nanocomposite ETL is used. In addition, the operational frequency of the optimal PeLED is up to 1.5 MHz.